INDICATOR AND ANALYSES OF THE PREPARATION AND PHYSICAL DEVELOPMENT OF 7-10 YEARS OLD BOYS AND GIRLS - Salimov G’.M (Research Parks Publishers, 2021)
The article examines indicator and analyses of the preparation and physical development of 7-10 years old boys and girls and their analyzes are given in chart. The level of physical development and physical fitness of boys and girls prior to the experiment was analyze during mathematical-static indicators. The data in the charts show that as children grow older, the differences between all the organs forces of the body also increase. In these figures we obtained, it was observed that the left claw forces differ significantly from the right claw forces. It seems that the use of national action games, along with other natural factors, social and educational means has a great impact. At the same time, based on the new requirements for physical education lessons, it was found that good results can be achieved through the use of national folk movement games, relying on new pedagogical technologies